Analisis Penerapan PSAP No.01 Tahun 2010 Terhadap Laporan Pertanggungjawaban Aparat Desa Dalam Pengelolaan Keuangan Dana Desa Di Kecamatan Bangsalsari Jember - Shovi Hasanah; Diana Dwi Astuti; Lia Rachmawati (JAKUMA : JURNAL AKUNTANSI DAN MANAJEMEN KEUANGAN, 2023)
ABSTRACT This study aims to find out whether villages in Bangsalsari District have implemented Government Accounting Standard Statement No. 01 on the accountability reports of village officials in managing village fund finances and to find out how the procedures made by villages in Bangsalsari sub-district in presenting village financial accountability reports. The type of research used in this research is qualitative research. The data used in this study are primary and secondary data. Data collection techniques were carried out using interview techniques and documentation studies. This research was conducted at the Bangsalsari District Village Office. The results of this study indicate that the application of Government Accounting Standards in Village Financial Accountability in this village has not been fully said to be good because there are still some financial reports that are not made by the village government and the procedure for making village financial accountability reports is in accordance with which by making an Implementation Realization Accountability Report. APBDes, Village Regulations, Village Property Reports and Reports of Government and Regional Government Programs that enter the village.